Predicting the survival of primary biliary cholangitis patients - Ferreira, Diana (2022)
Data are available in a publicly accessible repository that does not issue DOIs. Publicly available datasets were analysed in this study. These data can be found here: https://www.kaggle.com/jixing475/mayo-clinic-primary-biliary-cirrhosis-data (accessed on 1 July 2022).